Relationship between Mothers’ Perceptions of Toddlers and Complete Basic Immunization in Jelun Village, Banyuwangi - Harjono, Mohammad Fikriansyah (LPPM Universitas Dhyana Pura, 2025)
Complete basic immunization is an essential health program to prevent vaccine-preventable diseases. However, the coverage of complete basic immunization in Indonesia remains uneven, including in Jelun Village, Licin District, Banyuwangi. This study aims to examine the relationship between maternal perceptions and the completeness of basic immunization in Jelun Village, Banyuwangi. This study employs a descriptive quantitative design with a cross-sectional approach. Data was collected through interviews, questionnaires, and observations of 74 mothers with children aged 1-4 years in Jelun Village. The variables studied include maternal perceptions of complete basic immunization and immunization status. Data analysis was performed using bivariate analysis to determine the relationship between maternal perception and the completeness of basic immunization. The results show that 63.5% of mothers in Jelun Village have provided complete basic immunization to their children. Furthermore, a significant and strong relationship was found between maternal perception and the completeness of basic immunization (sig. = 0.000; c = 0,554). Positive maternal perceptions toward immunization are strongly associated with the completeness of basic immunization in children. Based on these findings, it is recommended to enhance education and health promotion to improve maternal perceptions of immunization, thereby increasing the coverage of complete basic immunization in Jelun Village.